Simultaneous Determination of Eight Chemical Components in Angelicae Sinensis Radix and Its Herbal Products by QAMS - Yu Zhang; Qian Li; Yanmei Feng; Lan Yang; Qi Wang; Yehong Guo; Daiyu Qiu (Journal of Analytical Methods in Chemistry)
A HPLC method has been developed for simultaneously detecting chlorogenic acid, ferulic acid, senkyunolide I, senkyunolide H, coniferyl ferulate, senkyunolide A, ligustilide, and levistolide A in Angelicae Sinensis Radix through quantitative analysis of multicomponents by single-marker (QAMS) method with ferulic acid as internal standard substance. The relative analysis correction factors of each component in Angelicae Sinensis Radix have good reproducibility under different chromatography conditions. In addition, no significant difference of results was found between quantitative analysis of multicomponents by single-marker (QAMS) method and external standard method in determining content of these components of different Angelicae Sinensis Radix and its 12 kinds of preparations. As a result, the established QAMS method for Angelicae Sinensis Radix analysis with ferulic acid as internal standard substance is accurate and feasible, which could be used as an effective and economical method to control quality of Angelicae Sinensis Radix and its herbal products.